Associations Between Dairy Intake, Body Composition, and Cardiometabolic Risk Factors in Spanish Schoolchildren: The Cuenca Study - Garcia-Hermoso, A (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
Full-fat dairy has been traditionally associated with obesity and cardiovascular disease (CVD); however, recent evidence shows that the amount of dairy intake might have a beneficial effect over these pathologies, regardless of their fat content. The aim of this study was to examine the association between the intake of dairy products (including milk with different fat contents) with both adiposity and serum lipid concentration, adjusted by cardiorespiratory fitness (CRF), in Spanish schoolchildren. A cross-sectional study of 1088 children, aged 8 to 11 years, was conducted in which anthropometric variables (body mass index (BMI), waist circumference (WC), fat mass percentage (FM%) and fat mass index (FMI)), blood lipid profile, and dairy intake (using a food frequency questionnaire), and CRF (through a 20-m shuttle run test) were measured. Results showed that children with lower BMI, WC, FM%, and FMI had higher whole-fat milk intake and lower skimmed and semi-skimmed milk intake than children with higher BMI, WC, FM%, and FMI. Children with normal levels of triglycerides and high density lipoproteins (HLD) cholesterol consumed more whole-fat milk and less reduced-fat milk than children with dyslipidemic patterns. These relationships persisted after adjustment for CRF. Our findings suggest that full-fat milk intake should be promoted in children without obesity or high cardiometabolic risk. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.